Transforming the Role of Teachers in the AI Era: An Analysis Critical to Competence Professionals and Needs Training in Indonesia - Widianingsih, Zeny (Asosiasi Persatuan Pengusaha Muda Teknik Informatika, 2025)
Transformation the role of teachers in the era of intelligence artificial intelligence (AI) becomes phenomenon important in dynamics Indonesian education . Changes technology demand shift paradigm from role traditional teacher towards role as facilitators , innovators , and users technology learning . However , the adoption of AI in education Not yet accompanied with improvement teacher competency in general evenly distributed , which causes challenge in management learning based technology . Research This aim to : (1) analyze form transformation the role of teachers in Indonesia due to AI development ; (2) evaluating competence professional teachers in context digitalization education ; and (3) identifying need relevant and sustainable teacher training . Methods study use approach qualitative-descriptive with analysis content literature scientific latest and supporting data from survey national fictitious . Data analyzed use approach thematic to competence teacher professionalism and dynamics digital training . The results show that part big teacher still dominant in competence pedagogy traditional (82%) and only few are able leveraging AI in learning (28%). It was also found that need training covers three main domains : digital literacy , mastery AI pedagogy , and development curriculum innovative . Competency gap and lack of system adaptive training​ become obstacle main transformation this . Therefore that , it is needed synergy policies , training contextual , and collaborative cross sector use push role new teachers in the AI era maximum .